(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
In existing spinning systems in the processing of natural, artificial and synthetic fibers into yarn, the main task of the technological process is to obtain a ribbon, rovings and yarn uniform in structure and properties by folding and drawing. The article studies and obtained analytical dependences for calculating the angle of flow around the exhaust cylinder by the lobe on the spinning line of ring spinning machines. Based on research, we can conclude that the optimal condition for reducing the unevenness of the product being drawn in the exhaust device of ring spinning machines equipped with a new exhaust device will be minimal.